Determination of toxigenic capacity by reverse transcription polymerase chain reaction in coagulase-negative staphylococci and Staphylococcus aureus isolated from newborns in Brazil - de Oliveira Calsolari, Regina Adriana; Pereira, Valeria Cataneli [UNESP]; Araujo Junior, Joao Pessoa [UNESP]; Ribeiro de Souza da Cunha, Maria de Lourdes [UNESP] (Wiley-Blackwell, 2011)
Staphylococcus spp. are frequently found in hospital environments and are associated with a wide variety of infections. Various virulence factors are responsible for the pathogenicity of staphylococci, among which staphylococcal enterotoxins and TSST-1 (toxic-shock syndrome) are noteworthy. In this study, 90 samples of Staphylococcus aureus and 90 samples of coagulase-negative staphylococci (CNS) isolated from different clinical materials were investigated by polymerase chain reaction (PCR) in order to study the genes encoding staphylococcal toxins A (sea), B (seb), C (sec-1), D (sed) and TSST-1(tst). The samples shown to be positive for the presence of one or more genes were tested for their capacity to express mRNA encoding the respective toxins by reverse transcription-PCR (RT-PCR). As regards the CNS species, S. epidermidis was the most frequently isolated, corresponding to 71.1% of the total number of samples of CNS investigated. One hundred and eight samples were positive according to PCR, of which 59 (54.6%) were S. aureus and 49 (45.4%) were CNS. S. aureus showed toxigenic genes for all classes of toxins investigated whereas CNS showed all genes except for that of toxin D. Assessment of mRNA expression by RT-PCR showed 43 positive samples, 37 (86.0%) S. aureus samples producing SEA, SEB, SEC, SED and/or TSST-1 and six (14.0%) CNS samples producing SEA and SEC. RT-PCR and sequencing of PCR products confirmed the toxigenic capacity of S. epidermidis and S. lugdunensis, indicating the need for greater attention to such microorganisms when they are isolated from infectious processes.
Keywords: coagulase-negative staphylococci; RT-PCR; Staphylococcus aureus; toxins